2003
DOI: 10.1034/j.1600-0897.2003.00018.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer (NK) Cell Receptors' Repertoire in Couples with Recurrent Spontaneous Abortions

Abstract: Women with alloimmune abortions have a limited inhibiting KIR repertoire and such miscarriages may occur because trophoblastic HLA class I molecules are recognized by decidual NK cells lacking the appropriate inhibitory KIRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
2
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 38 publications
5
45
2
4
Order By: Relevance
“…RSA patients seem to show a higher prevalence of B haplotypes when compared with A haplotypes, and individuals with BB genotypes might be at a greater risk for spontaneous miscarriages than those having AA or AB genotypes [61,62].…”
Section: Nk Cells: Harmful In Pregnancy?mentioning
confidence: 96%
“…RSA patients seem to show a higher prevalence of B haplotypes when compared with A haplotypes, and individuals with BB genotypes might be at a greater risk for spontaneous miscarriages than those having AA or AB genotypes [61,62].…”
Section: Nk Cells: Harmful In Pregnancy?mentioning
confidence: 96%
“…Studies of NKR polymorphism and the HLA-C alleles expressed on the trophoblasts aimed at uncovering the consequences that the various combinations might have on pregnancy outcome have been reported. In one preliminary study, 26 childless couples with two or greater incidences of abortions presenting alloimmune abnormalities were compared with 26 normal couples (33). It was found that the percentage of women with alloimmune recurrent spontaneous abortions lacking inhibitory NKRs carried by their husbands and/or having a limited inhibitory KIR repertoire was much higher than that for women with successful pregnancy outcomes, thereby arguing for a role of the inhibitory KIRs in protecting the fetus.…”
Section: Mechanisms Of Fetomaternal Tolerancementioning
confidence: 99%
“…[25][26][27] NK hücre reseptörlerinin araştırıldığı bir çalışmada, tekrarlayan spontan düşükleri olan kadınlarda inhibitr KIR'lerin kontrollere göre daha az olduğu bulunmuştur. 27 Bu çalışmada, alloimmün düşüklerde daha az sayıda inhibitör KIR olduğu ve bu düşüklerin trofoblastik HLA klas I moleküllerinin uygun inhibitör KIR olmayan uNK hücreleri tarafından tanınmasın-dan kaynaklandığı kanısına varılmıştır. Yan ve ark.nın yaptığı çalışma bu çalışma ile benzer sonuç-lar sunsa da Witt ve ark.nın sonuçları bu sonuçlarla uyum göstermemektedir.…”
Section: Discussionunclassified